History and rationale for the development of an international evaluation programme - Helder, Theo (Henry Stewart Talks, 2012)
Countries with a GLP monitoring program (1989): the GLP panel, OECD, The OECD MAD decision C(81)30 (final), OECD council decision-recommendation C(89)87(final), Annex I, II and III, Mutual acceptance of data, Objective of the mutual joint visit (MJV) pilot project, Working group on GLP, MJV pilot project, Programme of on-site evaluation visits